Eliminating concrete cover separation of NSM strengthened beams by CFRP end anchorage - Hosen, M.A.; Jumaat, Mohd Zamin; Islam, A.B.M.S.; Kamruzzaman, M.; Huda, M.N.; Soeb, M.R. (Techno-Press, 2015)
Upgrading or strengthening of existing reinforced concrete (RC) infrastructure is an emerging demand nowadays. Near Surface Mounted (NSM) technique is very promising approach for flexural strengthening of RC members. However, premature failure such as concrete cover separation failure have been a main concern in utilizing this technique. In this study, U-wrap end anchorage with carbon fiber reinforced polymer (CFRP) fabrics is proposed to eliminate the concrete cover separation failure. Experimental programs were conducted to the consequence of U-wrap end anchorage on the flexurally strengthened RC beams with NSM-steel. A total of eight RC rectangular beam specimens were tested. One specimen was kept unstrengthened as a reference; three specimens were strengthened with NSM-steel bars and the remaining four specimens were strengthened with NSM-steel bars and U-wrap end anchorage using CFRP fabrics. A 3D non-linear finite element model (FEM) was developed to simulate the flexural response of the tested specimens. It is revealed that NSM-steel (with and without end-anchors) significantly improved the flexural strength; moreover decreased deflection and strains compared with reference specimen. Furthermore, NSM-steel with end anchorage strengthened specimens revealed the greater flexural strength and improve failure modes (premature to flexure) compared with the NSM-steel without end anchorage specimens. The results also ensured that the U-wrap end anchorage completely eliminate the concrete cover separation failure.